Kidney outcomes using a sustained ≥40% decline in eGFR: A meta‐analysis of SGLT2 inhibitor trials. Issue 8 (15th June 2021) - Cherney, David Z. I.; Dagogo‐Jack, Samuel; McGuire, Darren K.; Cosentino, Francesco; Pratley, Richard; Shih, Weichung J.; Frederich, Robert; Maldonado, Mario; Liu, Jie; Wang, Shuai; Cannon, Christopher P.; ,
Abstract: Background: A recent meta‐analysis of sodium–glucose cotransporter 2 (SGLT2) inhibitor outcome trials reported that SGLT2 inhibitors were associated with reduction in the risk of adverse composite kidney outcomes, with moderate heterogeneity across the trials; however, the endpoints were defined differently across the trials. Hypothesis: The apparent heterogeneity of the meta‐analysis of kidney composite outcomes of SGLT2 inhibitor trials will be substantially reduced by using a consistent assessment of sustained ≥40% decline in eGFR/chronic kidney dialysis/transplantation/renal death across trials. Methods: We performed a meta‐analysis of kidney composite outcomes from the four SGLT2 cardiovascular outcome trial programs conducted in general type 2 diabetes mellitus populations, which included, as a surrogate of progression to kidney failure, a sustained ≥40% decline in eGFR along with kidney replacement therapy and kidney death. The trials assessed were VERTIS CV (NCT01986881), CANVAS Program (NCT01032629 and NCT01989754), DECLARE‐TIMI 58 (NCT01730534), and EMPA‐REG OUTCOME (NCT01131676). Results: Data from the trials comprised 42 516 individual participants; overall, 998 composite kidney events occurred. SGLT2 inhibition was associated with a significant reduction in the kidney composite endpoint (HR 0.58 [95% CI 0.51–0.65]) and with a highly consistent effect across the trials (Q statistic p = .64; I 2 = 0.0%). Conclusions: Our meta‐analysis highlights the value of using similarly defined endpoints across trials and supports the finding of consistent protection against kidney disease progression with SGLT2 inhibitors as a class in patients with type 2 diabetes mellitus who either have established atherosclerotic cardiovascular disease or are at high cardiovascular risk with multiple cardiovascular risk factors.